Guía virtual interactiva utilizando inteligencia artificial para el recorrido virtual del museo del cantón Guano. - Jaramillo Castillo, Kelvin Javier (2024)
The objective of this research was to implement an interactive virtual guide using artificial intelligence (AI) for the virtual tour of the Guano Canton Museum. The SUM methodology, specific for the development of video games, was used to ensure the quality and efficiency of the project, which focused on evaluating the usability of the virtual guide following the ISO/IEC 25010 standard. Structured surveys were conducted with seventh semester IT students to collect data on information clarity, response time, visual appeal, percentage of learnability, operability and error protection. The results showed high satisfaction among users in all parameters evaluated. The integration of AI, through the use of Convai's API, enabled the creation of interactive and personalized experiences, facilitating the generation of dynamic content and real-time interaction. The virtual guide obtained an overall usability percentage of 92.2%, standing out as a highly usable and effective tool. In the conclusions, the potential of AI technologies to enhance the user experience in virtual tours, providing interactivity and relevance in the information presented, was confirmed. Convai's API was shown to be an effective solution for generating dynamic content and adapting to user questions, ensuring an interactive and accurate experience. The usability evaluation validated the effectiveness of the application, ensuring a positive and reliable experience for users.